2000
DOI: 10.1034/j.1399-3003.2000.016003437.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of nitric oxide synthase by nasal decongestants

Abstract: The nasal decongestants oxymetazoline and xylometazoline are frequently used in the topical treatment of rhinitis and sinusitis. As nitric oxide (NO) is thought to play a role in inflammation of the upper respiratory tract, the aim of this study was to examine the in vitro effects of these compounds on the activity and the expression of NO producing enzymes, including the inducible form of NO synthase (iNOS) and the constitutive isoform of NO synthase (cNOS).Experiments concerning the effects of both compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
1
18
0
1
Order By: Relevance
“…In addition to being an a-agonist, oxymetazoline has been shown to have various antioxidative and anti-inflammatory properties. [8][9][10][11][12] Whether any of these effects contributed to our results is unknown. The oxymetazoline was dosed once daily at night.…”
Section: Discussionmentioning
confidence: 57%
“…In addition to being an a-agonist, oxymetazoline has been shown to have various antioxidative and anti-inflammatory properties. [8][9][10][11][12] Whether any of these effects contributed to our results is unknown. The oxymetazoline was dosed once daily at night.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, Westerveld et al (2000) referred that 0.3 mM oxymetazoline inhibited inducible nitric oxide synthase in a cellular system with rat alveolar macrophage cell line NR 8383, whereas the constitutive nitric oxide synthase was not affected. Oxymetazoline was also a potent inhibitor of lipid peroxidation and excellent hydroxyl radical scavenger (Westerveld et al, 1995).…”
Section: Discussionmentioning
confidence: 95%
“…Bjerknes and Steinsvag (1993) reported that compounds such as oxymetazoline chloride and xylometazoline chloride inhibit human neutrophil functions including actin polymerization, phagocytosis, and oxidative burst. Furthermore, Westerveld et al (2000) showed that oxymetazoline strongly inhibits the expression of the inducible form of nitric oxide synthase and speculated that nasal decongestants might offer a new tool to reduce inflammatory mechanisms. Westerveld et al (1995) also referred to antioxidant actions of oxymetazoline by showing that this compound is a potent inhibitor of microsomal lipid peroxidation and an excellent hydroxyl radical scavenger.…”
mentioning
confidence: 99%
“…Westerveld et al have also reported that NDs have dose-dependent inhibitory action on total iNOS activity which appears to be beneficial because inducible NO synthase activity may exacerbate the inflammatory process. 13 They also reported that NDs in vitro appear to have additional benefit in the treatment of upper respiratory tract infection.…”
Section: Discussionmentioning
confidence: 97%